2020
DOI: 10.1039/d0an00476f
|View full text |Cite
|
Sign up to set email alerts
|

Identification of methicillin-resistant Staphylococcus aureus bacteria using surface-enhanced Raman spectroscopy and machine learning techniques

Abstract: To combat antibiotic resistance, it is extremely important to select the right antibiotic by performing rapid diagnosis of pathogens. Traditional techniques require complicated sample preparation and time-consuming processes that are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 54 publications
0
76
0
Order By: Relevance
“…Although the typical procedure normally takes 3–4 days or even longer for fastidious bacteria on average to obtain the final AST results ( Han et al, 2020 ), with MALDI-TOF MS-based approaches, i.e., for positive blood culture bottles, a result can be obtained after <24 h, in some cases also the same day ( Verroken et al, 2014 ). Due to its simple operations, RS, especially SERS, has been used for testing antibiotic resistance phenotypes in many bacterial species, such as E. coli ( Chang et al, 2019 ), S. aureus ( Uysal Ciloglu et al, 2020 ), and Pseudomonas aeruginosa ( Li et al, 2019 ). A variety of signatures have been observed in terms of bacterial antibiotic resistance and susceptibility, which could be used for rapidly identifying resistance to sublethal concentrations of antibiotics ( Galvan and Yu, 2018 ; Han et al, 2020 ).…”
Section: Antibiotic Resistance Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the typical procedure normally takes 3–4 days or even longer for fastidious bacteria on average to obtain the final AST results ( Han et al, 2020 ), with MALDI-TOF MS-based approaches, i.e., for positive blood culture bottles, a result can be obtained after <24 h, in some cases also the same day ( Verroken et al, 2014 ). Due to its simple operations, RS, especially SERS, has been used for testing antibiotic resistance phenotypes in many bacterial species, such as E. coli ( Chang et al, 2019 ), S. aureus ( Uysal Ciloglu et al, 2020 ), and Pseudomonas aeruginosa ( Li et al, 2019 ). A variety of signatures have been observed in terms of bacterial antibiotic resistance and susceptibility, which could be used for rapidly identifying resistance to sublethal concentrations of antibiotics ( Galvan and Yu, 2018 ; Han et al, 2020 ).…”
Section: Antibiotic Resistance Profilingmentioning
confidence: 99%
“…Due to the complexity of Raman spectra, statistics and machine learning algorithms, rather than traditional linear analysis, are normally involved in data processing procedures. So far, many machine learning methods have been introduced into Raman spectra analysis, such as artificial neural network, deep learning, and Monte Carlo estimation ( Lu et al, 2012 ; Moawad et al, 2019 ; Lussier et al, 2020 ; Uysal Ciloglu et al, 2020 ). In the rapid characterization of Staphylococcus , Rebrošová et al (2017) compared three machine learning methods, namely, linear discriminant analysis, one nearest neighbor, and support vector machine (SVM), all of which showed efficient identification of staphylococci using RS with high accuracy.…”
Section: Computational Analysis Of Raman Spectramentioning
confidence: 99%
“…The antibiotic resistance of MRSA and MSSA was confirmed the presence or absence of mec A gene using the Polymerase Chain Reaction (PCR) technique. Furthermore, the disc diffusion method was also used for the antibiotic resistance confirmation and details can be found in our previous study 15 . According to PCR and disc diffusion method results methicillin resistance was found in all MRSA bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the SERS technique requires advanced data processing algorithms to capture these minor differences. A vast majority of publications have reported that machine learning techniques can be employed to discriminate antibioticresistant and susceptible bacteria by using data obtained from SERS [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation